(untitled) (Journal of the Bangladesh Agricultural University, 2010)
Five varieties of diseased onion samples, four local (Taherpuri, Faridpuri, Kalashnagari, and Zitka) and one Indian (Pusa Red) were collected from different markets of Mymensingh, to isolate and identify the associated fungi. Five different fungal species belonging to three genera were repeatedly isolated. Healthy looking and diseased onions were kept at room temperature. The population of associated fungi increased proportionately with the duration of storage period. The isolated fungi were Aspergillus niger, Aspergillus flavus, Penicillium spp., Fusarium oxysporum and Fusarium moniliforme. Healthy onion bulbs were inoculated (with injury and without injury) with these fungi. Individual fungi produced distinguishable symptom of disease in incubation chamber at 22-23°C temperature. After 30 days of inoculation, bulbs showed comparatively low amount of disease development than those at 60 and 90 days. Maximum disease development was found in the variety Pusa Red (with injury) and it was minimum in Zitka variety (without injury). Keywords: Fungi; Onion; Disease development DOI: 10.3329/jbau.v6i2.4818 J. Bangladesh Agril. Univ. 6(2): 245-251, 2008